Budaya Catur Purusa Artha Memoderasi Love of Money dan Sifat Machiavellian, Terhadap Indikasi Fraud - Ningsih, Komang Risa Rahayu; Budiartha, Ketut; Sujana, I Ketut; Putra, I Nyoman Wijana Asmara (E-Jurnal Akuntansi; Vol 32 No 7 (2022), 2022)
This study aims to analyze the effect of Love of money and Machiavellian nature on indications of fraud, as well as to test whether the Catur Purusa Artha culture is able to weaken this influence. The research was conducted on GSM BUMDes spread across Buleleng Regency with a total sample of 95 respondents who were analyzed by SEM PLS 3.0. The results showed that love of money and machiavellian nature had a positive effect on indications of fraud. This means that the higher the love of money owned by BUMDes managers, the higher the tendency to indicate fraud. The Catur Purusa Artha culture is able to weaken the influence of love of money on indications of fraud. Which means that the attitude of Love of money accompanied by the practice of good values ??of Catur Purusa Artha can reduce the negative influence of the attitude of Love of money on indications of fraud. Meanwhile, the Catur Purusa Artha culture does not moderate the Machiavellian influence on indications of fraud. This means that Catur Purusa Artha does not have an impact on the Machiavellian influence on indications of fraud. Keywords: Love of Money ; Machiavellian; Catur Purusa Artha Culture; Fraud.